SWOT ANALYSIS OF SAVING PRODUCTS IB HIJRAH HAJI PT. BANK MUAMALAT INDONESIA SUPPORTING BRANCH - vera vera; ikhwanuddin harahap; Windari windari; arti damisa (Journal Of Sharia Banking, 2021)
One of the obstacles for the Mandailing Natal community to go on a pilgrimage is the high cost of going on a pilgrimage. IB Hijrah Haji Savings is a savings account that makes it easier for people to visit the Baitullah. However, not many people know about this IB Hijrah Haji savings product, seen from the number of IB Hijrah Haji savings customers who experience fluctuations every month in 2018. The problem formulation in this study is how to analyze the SWOT product of the IB Hijrah Haji Savings product PT. Bank Muamalat Indonesia Panyabungan Sub-Branch. The purpose of this study was to determine the development of the number of customers of IB Hijrah Haji Savings PT. Bank Muamalat Indonesia Panyabungan Sub-Branch. This research was conducted at PT. Bank Muamalat Indonesia Panyabungan Sub-Branch with qualitative-descriptive research method. The subjects of this research are employees of PT. Bank Muamalat Indonesia Panyabungan Sub-Branch, IB Hijrah Haji savings customers and the Mandailing Natal community. Collecting data using interview techniques and direct and indirect observations of objects related to the researched and documentation. Meanwhile, data analysis used the following techniques: data editing, data reduction and data decryption. The results of the study using the SWOT Matrix showed that PT. Bank Muamalat Indonesia Panyabungan Sub-Branch has strengths which consist of: fairly good and fast service, service to deliver prospective pilgrims and free Hajj rituals, free administration fees, free insurance. Weaknesses of IB Hijrah Haji savings, namely: lack of human resources marketing IB Hijrah Haji savings products, product promotion is still lacking. The savings opportunities for IB Hijrah Haji are: people who are predominantly Muslim, increasing customer interest in using this product, strategic location. Meanwhile, the threats of IB Hijrah Haji savings are: product competition that is getting tighter, locations between banks that are close to each other.